Self-Confidence and Strategic Deterrence - Gary Charness; Aldo Rustichini; Jeroen van de Ven (Tinbergen Institute, 2011)
We examine factors that may contribute to 'overconfidence' in relative ability on an intelligence test. We test experimentally for evidence of self-esteem concerns and instrumental strategic concerns. Errors in Bayesian updating are rare when the information does not involve own relative ability, but far more common when it does, suggesting self-esteem issues. There is also strong evidence that males state higher levels of confidence in relative ability when this precedes a tournament; as entry is predicted by relative confidence, this can be an effective deterrent. Inflating confidence can be part of an equilibrium strategy, providing a rationale for strategic overconfidence.
Keywords: A12; C91; D03; D82; 330; Self-confidence; overconfidence; strategic deterrence; unconscious behavior; selfdeception